Starch grain analysis on Late Iron Age grindstones from South Africa - Langejans, G. H. J. (Southern African Humanities, 2021)
This study examined starch grains from a number of Late Iron Age grindstones to verify the presence of maize at Thabazimbi 2427 CB14, a sixteenth/seventeenth century site in Limpopo Province, South Africa. To analyse the archaeological samples, it was necessary to create a comparative collection and secondly a starch grain typology. Typical starch grain assemblages helped to identify different storage organs, such as tubers, beans and seeds. I analysed samples from 18 grindstones, including some from Mgoduyanuka, the oldest site so far to yield carbonised maize cobs. Because maize and sorghum overlap in grain shape and size, and because the archaeological samples contained few starch grains, I was unable to verify the presence of maize at the Thabazimbi site. To cite this article: Langejans, G. H. J. 2006. Starch grain analysis on Late Iron Age grindstones from South Africa. Southern African Humanities 18 (2): 71-91.